Habitat, morfologia branquial e osmorregulação das arraias de água doce da bacia amazônica (Elasmobranchii: Potamotrygonidae) - Duncan, Wallice Luiz Paxiuba (2008)
The relationship between functional morphology of the gills, osmoregulatory physiology, and habitats of the freshwater stingrays (family Potamotrygonidae) was investigated. Potamotrygonid gills have a rather unique external and internal anatomy and organization compared with other marine and/or euryhaline rays. The filaments on the hemibranchs are usually longer and numerous in the second arch. A protuberance was observed on the leading edge of the filaments. The epithelium that covers the gill filaments and lamellae is composed primarily of pavement cells (PVCs), mucous cells (MCs) and chloride cells (CCs). The PVCs showed PAS-positive reactivity. In addition, studies using transmission electron microscopy (TEM) indicate that PVCs possess subapical secretory granules or vesicles that contain mucous material. Large mucous cells were observed with Alcian blue and PAS reaction suggesting the presence of acid and neutral mucopolysaccharides, respectively. Particular attention was focused on the chloride cells. Na+/K+ -ATPase-rich cells (chloride cell, CC-NKA) were frequently found on the trailing edge and in the interlamellar spaces. They were also found on the lamellae, although generally towards the base. The number of CC-NKA and Na+/K+ -ATPase activity were greatest in arch IV compared with the other branchial arches. The basolateral membrane of the chloride cell does has moderate infoldings, and they are likely the site of Na+/K+ -ATPase activity. A surprising result was observed in Potamotrygon sp., in which chloride cells were arranged in large groups in the interlamellar region, not observed in other potamotrygonid species. This multicellular complex of chloride cell is certainly unusual, and may provide a micro-environment suitable to ion uptake from the acidic and ion-poor water of the Rio Negro basin. Potamotrygonid stingrays exhibit typical teleostean body fluid chemistry. These results were analyzed based on the organism-environment interaction. Amazonian rivers, such as Rio Amazonas, Rio Negro, and Rio Tapajós are spatially heterogeneous in their physical and chemical features. In this regard, it is apparent that some distribution patterns of the family Potamotrygonidae may be related to the type of water (e.g white, black and clearwater). The hydrographic barrier hypothesis was tested in Potamotrygon sp. In this ray, plasma [Na+], [Cl-], osmolality and kidney Na+/K+ -ATPase activity decreased after acclimatization to water of the Rio Branco compared to Rio Negro-acclimatized animals. These findings suggest that whitewater-associated changes on the ion and plasma osmolality are due to reduction in the renal Na+/K+ -ATPase activity resulting in an ion loss to the environment. In our biogeographic scenario, some water types may act as an expressive hydrographic barrier for the isolation of endemic potamotrygonid species. On the other hand, Paratrygon aiereba, a widespread stingray that lives in white, clear and blackwaters in the Amazon basin exhibited some physiological differences related to the aquatic environment. Plasma osmolality, urea and ion concentration were higher in whitewater, as compared to blackwater rays. This fact may be explained as an example of phenotypic plasticity, usually expressed in aquatic animals in environments with different aquatic compositions.